Optimizing palliative care and support for pets –perspectives of the pet-parent and the veterinarian - Lam, Wendy W. T.; Fielding, Richard; Choi, Lok Yi (Frontiers in Veterinary Science, 2023)
As animals benefit from improved chronic disease care, more pet-parents and veterinarians face issues of late life and terminal care. Management of life limiting disease commonly considers the timing of euthanasia, often overlooking the role of supportive palliative care. Necessary communications between vet and pet-parents are rarely emphasized. However, as in human palliative care, the central role of good communications is critical. In particular, three communication elements are primary, namely: empathic communication and shared decision-making; managing progressive symptoms, and; advanced directives. Moreover, focusing only on euthanasia can easily discount the profound emotional legacy of bereavement. This Perspective illustrates how communications policies derived from human palliative care are exemplified in the management of a case of canine lung cancer, to the wider practice benefits of pets, pet-parents and veterinary practice staff.